2018
DOI: 10.37358/rc.18.7.6393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and in vitro Biological Evaluation of a New Schiff Base Derived from Drug and its Complexes with Transition Metal Ions

Abstract: New series of copper (II), cobalt (II), zinc (II), nickel (II), manganese (II), iron (II) complexes of a novel Schiff base were prepared by the condensation of sulphadizine and pyridoxal hydrochloride. The ligand and metal complexes were characterized by utilizing different instrumental procedures like microanalysis, thermogravimetric examination and spectroscopy. The integrated ligand and transition metal complexes were screened against various bacteria and fungus. The studies demonstrated the enhanced activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The integrated ligand and transition metal complexes were screened against various bacteria and fungus. The studies demonstrated the enhanced activity of metal complexes against reported microbes compared to free ligand [11].…”
mentioning
confidence: 94%
“…The integrated ligand and transition metal complexes were screened against various bacteria and fungus. The studies demonstrated the enhanced activity of metal complexes against reported microbes compared to free ligand [11].…”
mentioning
confidence: 94%
“…Schiff bases have been regarded as important ligands due to their contribution to coordination chemistry due to their variable bonding, structural possibilities, and their applications in several fields; they can be simply prepared and associated with many metal ions without any requirement of purification because water is the only byproduct of condensation. [ 1–3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases have been regarded as important ligands due to their contribution to coordination chemistry due to their variable bonding, structural possibilities, and their applications in several fields; they can be simply prepared and associated with many metal ions without any requirement of purification because water is the only byproduct of condensation. [1][2][3] They have an amine group, similar to the natural biological systems, so they have different applications and functions as observing the conversion mechanism, racemization reaction in biological systems, biological probes, acting as antitumor, anti-HIV, antibacterial, antifertility, antimosquito larval, anti-inflammatory, and anticancer, DNA cleaving agents. [4][5][6] Beside biological activities, Schiff bases are also used as dyes, pigments, catalysts, and corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases were discovered first time by the chemist Hugo Schiff in 1864 [1]. These are condensation products of carbonyl compounds and amines [2], also called as imine or azomethine due to (-HC=N-) functional group [3], here nitrogen atom serves as bonding molecule for complexation.In azomethine derivatives, the C‚N linkage is essential for biological activity [4,5], several azomethine have been reported to possess remarkable antibacterial, antifungal, anticancer and antimalarial activities [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%